Out of the Mouths of Babes: Imitation, Gaze, and Intentions in Infant Research: the "Like Me" Framework - Meltzoff, Andrew (Mimesis and science, 2011)
In the past decade, we witnessed an overturning of one of the most pervasive scientific myths about man?s original nature?the myth of the asocial infant. The classical scientific views offered by Freud, Skinner, and Piaget proposed that the newborn is at first cut off from others and gradually becomes ?socialized.? Freud and his followers proposed a distinction between a physical and psychological birth. When a child is born, there is a physical birth but not yet an interpersonal one. The baby is like an unhatched chick, incapable of interacting as a social being because a ?barrier? leaves the newborn